(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The new EU Novel Food Regulation and the problems derived from the previous legislation (Reg. 258/97) represent a perfect example of the challenges the legislator has to face in the specific agri-food sector: first of all, the need to find a correct balance between food safety and innovation, strictly linked with the efforts to protect the environment and the future generations’ needs.